Traditional and Recent Approaches for the Development of Animal Vaccines. A Review - Arslan Shuja, Javed Anver Qureshi, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2023)
Results: The discovery of antigen/gene delivery systems has facilitated the development of novel prophylactic and therapeutic veterinary vaccines. Uses several bioinformatics algorithms to predict antigen localization and it has been successfully applied to immunize against many veterinary diseases. Vectors and pathogens that may lead to emergent diseases in animals. Preventing transmission of emerging infectious diseases at the animal–human interface is critically important for protecting the world population from epizootics and pandemics. Hence, there is a need to develop new vaccines to prevent diseases in animals. An area of veterinary vaccination that needs more research and discussion is vaccine interference. The phrase itself is ambiguous and might mean either a condition in which immunization against one disease may weaken the protective immunity established by immunization against another, or a circumstance in which the presence of maternally derived antibodies prevent immunization in newborn animals. Practical implication: This study will provide awareness among community about veterinary vaccines and will develop a disease-free state for pets.Vetrinary vaccines not only prevent diseases in animals but also stops their spread among humans. Keywords: Vaccines, Toxin, Immunization, Antibodies, Antigen, Host.